Pemberian Makanan Tambahan Sebagai Upaya Pencegahan Stunting Di Kelurahan Ranggamekar - Irvan Maulana; Azmi Thufail (Universitas Pendidikan Indonesia, 2023)
This stunting occurs especially in children under five and is one of the factors that can hinder growth. Stunting is a condition where children under five cannot grow normally, where children experience obstacles in their physical, brain and other organ development. Providing Supplementary Food (PMT) is carried out to overcome the problem of malnutrition at the age of toddlers. PMT is not a substitute for the main daily food for toddlers aged 6-59 months. The principles are given in the form of food or local food ingredients, as additional food, to meet the nutrition of target toddlers, activities outside the health center with a community empowerment approach, qualitative descriptive (Moleong, 2005), namely a research approach where the data collected is in the form of words- words, pictures and not numbers. This data can be obtained from interviews, field notes, photos, video tapes, personal documentation, notes, or memos and other documentation (Akay et al., 2021). At a coordination meeting with the South Bogor Community Health Center together with posyandu cadres discussing the stunting prevention program in Ranggamekar Village, there were 2 children who were free from the category of children experiencing stunting. The stunting prevention program continues to be carried out to achieve one goal, namely